KEMATANGAN KERJA DAN KINERJA MENGAJAR GURU SEKOLAH DASAR PESERTA PROGRAM D.2 PENYETARAAN TATAP MUKA DI BALI - Oka, A.A. Ketut (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
This research study was to find out the association bebteen the work maturiv, defined in ternts of teacher abilitv to think abstractlv ancl commit to the assigned tasks, and the quality of their teaching performances, defined as the planned behmiors of doing teaching-learning processes. her,ihis teachtn capacity to generate students’learning in the classroom. To what extend teacher maturity correlate to teaching performances u:as the main problem to inr.,estigate within the contexts of the primary school teacher in-servicetraining for a D-2 equivalent qualification. The two dimensions of teacher maturity include abstract thinking ability and work commitntent held bv the primary school teachers. Teacher maturitv, then, classified into three categorie.s: low, medium, and high. It Was expected lhat teacher maturitt’ leyel would associate with teacher performances classtfied into good. dverage, and poor. Accordingly a kind ofa 3 by 3 dimension was designed to answer the proposed problem. Two hundred and rwenty primarv school teachers participating in an in-service program to obtained a D-2 equivalent qualification proportionally randomlv selected were included into this study. .,1 set o.f questionnaires was Developed and administered to the participating teachers in this research. The data were analyzed using a contingency, correlation method. The study found a signrficant relationship, association between the level of teacher maturity and their level of teaching performances.